Antimicrobial resistance and related issues: An overview of Bangladesh situation (Bangladesh Journal of Pharmacology, 2014)
The present study was designed to understand Bangladesh situation about antimicrobial resistance. Half of the Escherichia coli, Staphylococcus aureus, Pseudomonas and Klebsiella showed resistance against older and common antimicrobials. Most (50%) common reasons to prescribe antimicrobial are fever, respiratory and urinary tract infection. About 70% prescriber mentioned diagnostic uncertainty and emergence of resistance as causes for increase in antimicrobial prescribing. 51.9% of prescribers opined that physicians prescribe antimicrobial more than the actual need. About two-third of 5th year medical students answered correctly on different issues related to antimicrobials and resistance. Antimicrobial and resistance received little emphasis in Pharmacology and Microbiology written questions at both undergraduate (0.7 to 16.1%) and postgraduate (0.9 to 18.4%) level. Print (0.02% to 2.0%) and electronic media (0.0 to 0.6%) attaches small importance on the issues. Nothing related to antimicrobials and measure to contain resistance were mentioned in related policy documents.